Peningkatan Motivasi Belajar Peserta Didik dalam Pembelajaran Daring Melalui Model Pembelajaran Discovey Learning dan Video Pembelajaran Kelas II Sekolah Dasar (Universitas Sebelas Maret, 2020)
Research is carried out by looking for gaps between expectations and reality or more easily understood looking for gaps between expectations and conditions in the field. The conditions of hope are of course much oriented on the part of the teacher who must be able to provide good learning according to expectations. To be able to achieve this, the teacher must understand the approaches, methods, models, strategies, techniques, the role of subjects, their functions and uses. The success of the learning process is largely determined by the ability of the teacher to manage the learning process.The role of education itself is to be able to improve the quality of human resources, realize general welfare and educate the nation's life. Educated people certainly have a better quality of life than those who are not educated, inner and outer well-being also affects it. An intelligent nation must have a society that has quality human resources as well. For that learning is very important for yourself and the environment. The importance of learning to learn (learning to learn) fosters an open attitude towards the changes and challenges of an increasingly modern and challenging globalization.